2020
DOI: 10.1016/j.jamda.2020.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Understated Cognitive Impairment Assessed with the Clock-Drawing Test in Community-Dwelling Individuals Aged ≥50 Years

Abstract: Objectives: To estimate the prevalence of understated cognitive impairment by administering the Clock-Drawing Test (CDT) to community-dwelling individuals aged ≥50, and to investigate the associated clinical phenotype. Design: A cross-sectional analysis of baseline data on community-dwelling individuals assessed at an outpatient clinic in the Paris region of France. Setting and Participants: Participants aged ≥50 (n=488, median age: 62.1) prospectively included in the SUCCEED survey between 2010 and 2014. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Correctly “orienting the minute hand” was found to be the most significant predictor of classification of MCI versus NCF. Our finding is consistent with the data from 2 studies (1 conventional and 1 digital) which reported that correct placement of the “minute arm” was the best predictor of amnesia in individuals with MCI [ 29 , 53 ]. Such comparable results support the adoption of the 3 digital CD Acc item factors in EOmciSS.…”
Section: Discussionsupporting
confidence: 92%
“…Correctly “orienting the minute hand” was found to be the most significant predictor of classification of MCI versus NCF. Our finding is consistent with the data from 2 studies (1 conventional and 1 digital) which reported that correct placement of the “minute arm” was the best predictor of amnesia in individuals with MCI [ 29 , 53 ]. Such comparable results support the adoption of the 3 digital CD Acc item factors in EOmciSS.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, here we found that the MoCA-Thai alone yielded an important separated of AD from aMCI. Studies on the VSS subdomain in the MoCA, as measured by the clock drawing and cube copying, reported some interesting results, as for example, that conceptual clock drawing errors detect cognitive decline most effectively [89-93]. Additionally, the clock drawing task has the ability to differentiate, at baseline, cognitively intact older adults who will develop dementia up to 2 years post-baseline as well as patients with MCI who will progress to dementia up to 6 years post-baseline [92-94].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the proportion of clock-drawing errors increased with increasing age, similar to other studies. [25][26][27] Regardless of the type of clock-drawing scoring method, males were significantly more likely to draw an abnormal clock. Other studies have found that females do worse on the clock drawing compared with males, different from our results.…”
Section: Discussionmentioning
confidence: 98%